Biodegradable nanocarriers coated with polymyxin B: Evaluation of leishmanicidal and antibacterial potential. - Juliana Souza Ribeiro Costa; Marília Medeiros; Edite Harumi Yamashiro-Kanashiro; Mussya Cisotto Rocha; Paulo Cesar Cotrim; Marco Antonio Stephano; Marcelo Lancellotti; Guilherme Diniz Tavares; Laura Oliveira-Nascimento (Public Library of Science (PLoS), 2019)
Most treatments of leishmaniasis require hospitalization and present side effects or parasite resistance; innovations in drug formulation/reposition can overcome these barriers and must be pursued to increase therapeutic alternatives. Therefore, we tested polymyxin B (polB) potential to kill Leishmania amazonensis, adsorbed or not in PBCA nanoparticles (PBCAnp), which could augment polB internalization in infected macrophages. PBCAnps were fabricated by anionic polymerization and analyzed by Dynamic Light Scattering (size, ζ potential), Nanoparticle Tracking Analysis (size/concentration), vertical diffusion cell (release rate), drug incorporation (indirect method, protein determination) and in vitro cell viability. Nanoparticles coated with polB (PBCAnp-polB) presented an adequate size of 261.5 ± 25.9 nm, low PDI and ζ of 1.79 ± 0.17 mV (stable for 45 days, at least). The 50% drug release from PBCAnp-polB was 6-7 times slower than the free polB, which favors a prolonged and desired release profile. Concerning in vitro evaluations, polB alone reduced in vitro amastigote infection of macrophages (10 μg/mL) without complete parasite elimination, even at higher concentrations. This behavior limits its future application to adjuvant leishmanicidal therapy or antimicrobial coating of carriers. The nanocarrier PBCAnp also presented leishmanicidal effect and surpassed polB activity; however, no antimicrobial activity was detected. PolB maintained its activity against E. coli, Pseudomonas and Klebsiella, adding antimicrobial properties to the nanoparticles. Thus, this coated drug delivery system, described for the first time, demonstrated antileishmanial and antimicrobial properties. The bactericidal feature helps with concomitant prevention/treatment of secondary infections that worst ulcers induced by cutaneous L. amazonensis, ultimately ending in disfiguring or disabling lesions.